Remarkable Service: a Guide to Winning and Keeping Customers for Servers, Managers, and Restaurant Owners - Culinary Institute of America; Gary Allen (New York Wiley, 2001)
The Culinary Institute has produced a clearly written, well-illustrated guide to restaurant service that also includes details of food and dining history to make this an unusually interesting didactic work. The text is designed for fine restaurants of all types, where diners are seated.
Age Group: Adult
Includes bibliographical references and index.
Keywords: Culinary; Nonfiction; Service; Restaurant management; Food service management